12-2x=-2(y-x)-12

Simple and best practice solution for 12-2x=-2(y-x)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-2x=-2(y-x)-12 equation:


Simplifying
12 + -2x = -2(y + -1x) + -12

Reorder the terms:
12 + -2x = -2(-1x + y) + -12
12 + -2x = (-1x * -2 + y * -2) + -12
12 + -2x = (2x + -2y) + -12

Reorder the terms:
12 + -2x = -12 + 2x + -2y

Solving
12 + -2x = -12 + 2x + -2y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + -2x + -2x = -12 + 2x + -2x + -2y

Combine like terms: -2x + -2x = -4x
12 + -4x = -12 + 2x + -2x + -2y

Combine like terms: 2x + -2x = 0
12 + -4x = -12 + 0 + -2y
12 + -4x = -12 + -2y

Add '-12' to each side of the equation.
12 + -12 + -4x = -12 + -12 + -2y

Combine like terms: 12 + -12 = 0
0 + -4x = -12 + -12 + -2y
-4x = -12 + -12 + -2y

Combine like terms: -12 + -12 = -24
-4x = -24 + -2y

Divide each side by '-4'.
x = 6 + 0.5y

Simplifying
x = 6 + 0.5y

See similar equations:

| -12y=2x-3 | | 3(3x+1)+4=-23 | | 7.4x+1y=801900000 | | P=2.6x+33.0 | | 4x+2x+3x-3= | | 9x+6+x=46 | | 9x+7=-23 | | 3-4(5-7x)=5(2x+5)-2 | | y+8=-(x-9) | | 50-7y=-14 | | 100+.30x=70+.50x | | 10(.4+.5)=4g | | 66365/6=x | | 10(.04+.05g)=4g | | (-6)-(7)-(3)= | | y+5=-(x+4) | | 72-10n=-8 | | 6x-9+5x=90 | | 6(3.5y-4.2)-2.75y=134.7 | | 2x-1=x-50 | | -x-3+3=-19 | | 4(15)+2= | | 3x+1+x-2=48cm | | 3x+12-2x=11 | | 7x-10-x=20 | | =[9X-2]/3X | | y+10=6(x+7) | | x^3-ix^2+2ix+2=0 | | 7(3x+1)=-14 | | 9x+2y+7z-5x+3z-3y= | | .425= | | 10(x)2=490 |

Equations solver categories